T-cell-specific mTOR deletion in mice ameliorated CD4+ T-cell survival in lethal sepsis induced by severe invasive candidiasis. Issue 1 (1st January 2019) - Wang, Hao; Bai, Guangxu; Cui, Na; Han, Wen; Long, Yun
ABSTRACT: The mammalian target of rapamycin (mTOR) pathway can mediate T-cell survival; however, the role of this pathway in T-cell survival during fungal sepsis is unclear. Here, we investigated the role of the mTOR pathway in CD4 + T-cell survival in a mouse model of rapidly progressive lethal sepsis induced by severe invasive candidiasis and explored the possible mechanism. The decrease in CD4 + T-cell survival following fungal sepsis was ameliorated in mice with a T-cell-specific mTOR deletion, whereas it was exacerbated in mice with a T-cell-specific tuberous sclerosis complex (TSC)1 deletion. To explore the mechanism further, we measured expression of autophagy proteins light chain 3B and p62/sequestosome 1 in CD4 + T cells. Both proteins were increased in T-cell-specific mTOR knockout mice but lower in T-cell-specific TSC1 knockout mice. Transmission electron microscopy revealed that T-cell-specific mTOR knockout mice had more autophagosomes than wild-type mice following fungal sepsis. CD4 + T-cell mTOR knockout decreased CD4 + T-cell apoptosis in fungal sepsis. Most notably, the T-cell-specific mTOR deletion mice had an increased survival rate after fungal sepsis. These results suggest that the mTOR pathway plays a vital role in CD4 + T-cell survival during fungal sepsis, partly through the autophagy–apoptosis pathway.